Quantitative determination of zopiclone tablets «Sonovan» by spectrophotometry - S. L. Zagorodniy; S. O. Vasyuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. A new spectrophotometric method of assay zopiclone based on its interaction with bromtymol blue in acetone solution and measuring the absorption of the reaction product in the visible spectrum at a wavelength of 400 nm.